Introduction to free radicals and the oxygen paradox: oxidative stress in biology, aging & disease - Davies, Kelvin (Henry Stewart Talks, 2007)
The oxygen paradox, Oxygen origin, Free radicals, oxidants and oxidative stress, Sources of free radicals, Environmental toxins, Metabolic sources of free radicals: mitochondrial electron transport, phagocytes, peroxisomes, autooxidation, Medical and dental sources of free radicals: x-rays, g-rays, drugs, DNA damage and oxygen radical toxicity, Antioxidant compounds and enzymes, The dismutation of superoxide, Mechanisms of antioxidant enzymes, Antioxidant defense and repair systems, Removal of oxidized DNA bases and DNA repair, Lipolysis and the repair of oxidized lipids and lipid membranes, Selective proteolytic degradation of oxidized proteins, The LON protease, Adaptation to oxidative stress, Long-term effects of free radicals and oxidative stress: aging and disease